Cancer disrupts sex hormone-inflammation relationships: Analysis of ALI in males from NHANES 2007–2018 - Wenyao Xie; Zhenjun Zhang; Dan Zhao; Ya Zhang; Caiting Feng; Yicong Zhou (PLoS ONE, 2025)
Background To investigate the correlation between sex hormone levels and Advanced Lung Cancer Inflammation Index (ALI) in male cancer populations, and compare with non-cancer male populations, in order to elucidate the potential regulatory role of sex hormones in cancer-related inflammation. Methods We analyzed data from NHANES 2007–2018, including 11,280 males (1,135 cancer patients, 10,145 non-cancer controls). Serum testosterone and estradiol were measured using ID-LC-MS/MS. ALI was calculated as BMI(kg/m²) × serum albumin(g/dL)/ NLR. We employed weighted multivariate regression models with progressive adjustment for confounders and conducted stratified analyses by cancer status, age, and race/ethnicity. Restricted cubic splines explored non-linear relationships. Results Cancer patients had higher mean age (68.70 ± 11.85 vs. 48.36 ± 17.00 years), lower testosterone levels (377.35 ± 204.26 vs. 415.02 ± 183.92 ng/dL, P < 0.001), and lower ALI values (64.86 ± 118.61 vs. 72.68 ± 185.25, P = 0.053) than non-cancer controls. In fully adjusted models, each 10 ng/dL increase in testosterone was associated with a 3.0% decrease in ALI (OR=0.970, 95%CI: 0.962–0.978, P < 0.001), while each 1 pg/mL increase in estradiol was associated with a 60.3% increase in ALI (OR=1.603, 95%CI: 1.318–1.949, P < 0.001). Notably, these associations were significant only in non-cancer populations (testosterone: OR=0.97, P < 0.001; estradiol: OR=1.64, P < 0.001), and generally absent in cancer patients except for older cancer patients (≥60 years) where testosterone maintained a significant negative correlation with ALI (OR=0.96, P = 0.020). The testosterone-ALI negative correlation was strongest in younger individuals (20–39 years), while the estradiol-ALI positive correlation weakened with age. Estradiol exhibited significant non-linear relationship with ALI (P = 0.027), with multiple inflection points suggesting concentration-dependent effects. Conclusion This study systematically reveals for the first time the association between male sex hormone levels and ALI and the moderating effect of cancer status. The negative correlation between testosterone and ALI and the positive correlation between estradiol and ALI are significant in non-cancer populations but generally absent in cancer patients, suggesting that cancer may profoundly alter the relationship between sex hormones and inflammation. These findings suggest cancer may fundamentally alter sex hormone-inflammation relationships, providing new insights into hormone-mediated inflammatory regulation in health and disease.